Anti-hypotensive effect of “Yahom Navakot” in rats with orthostatic hypotension - Anjaree Inchan; Thanika Pathomwichaiwat; Tippaporn Bualeong; Sasipong Tipratchadaporn; Krongkarn Chootip (Journal of Traditional and Complementary Medicine, 2022)
Background and aim: Yahom Navakot (YN), is a Thai traditional medicine, consisting of 54 plants, for treating fainting and dizziness. Thus, YN might relieve orthostatic hypotension (OH) symptoms, but its therapeutic action is unclear. Therefore, this study evaluated YN in OH rats, using a head-up tilt test (HUT). Experimental procedure: Rats were anesthetized, and OH induced via a 90oHUT, before and after administering vehicle, a YN powder suspension (10, 100 mg/kg), a YN aqueous extract (100 mg/kg), and midodrine (5 mg/kg). The systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial blood pressure (MAP), pulse pressure (PP) and heart rate (HR) were determined via the carotid artery. Plasma noradrenaline (NA) was evaluated. YN-induced vasoconstriction of isolated rat aorta rings was determined using organ bath technique. Results and conclusion: Baseline BP increased with the 100 mg/kg YN powder suspension, the YN aqueous extract or midodrine, while HR decreased, compared with vehicle and control. 90oHUT rapidly reduced SBP, DPB and MAP, but increased HR, for control and vehicle-treated groups, but BP was steady with the 100 mg/kg YN powder suspension, the YN aqueous extract or midodrine. The 90oHUT-increase in HR was most pronounced with the 100 mg/kg YN powder suspension (the traditional formulation). This accords with increased plasma NA. YN also induced vasoconstriction in rat aorta via α1-receptor activation. Thus, the anti-hypotensive action of YN involved a stimulating effect on the heart and blood vessels via sympathetic activation. The results support the traditional use of YN and demonstrated the effectiveness of YN for OH prevention.